Cortical remodeling following suppression of endogenous estrogen with analogs of gonadotrophin releasing hormone. - Bell, K; Loveridge, N; Lindsay, P; Lunt, M; Garrahan, N; Compston, J; Reeve, J (1997)
The effects of estrogen suppression on osteonal remodeling in young women was investigated using transiliac biopsies (eight paired biopsies + four single pre; three single post biopsies) taken before and after treatment for endometriosis (6 months) with analogs of gonadotrophin releasing hormone (GnRH). Estrogen withdrawal increased the proportion of Haversian canals with an eroded surface (106%, p = 0.047), a double label (238%, p = 0.004), osteoid (71%, p = 0.002), and alkaline phosphatase (ALP) 116%, p = 0.043) but not those showing tartrate-resistant acid phosphatase (TRAP) activity (p = 0.25) or a single label (p = 0.30). Estrogen withdrawal increased TRAP activity in individual osteoclasts in canals with diameters greater than 50 microns (p = 0.0089) and also the number of osteons with diameters over 250 microns (p = 0.049). ALP activity in individual osteoblasts was increased but not significantly following treatment (p = 0.051). Wall thickness was significantly correlated with osteon diameter (p < 0.001). In a separate group of patients (four pairs + one post biopsy) on concurrent treatment with tibolone, there was no significant increase in the osteon density, cortical porosity, median canal diameter, or the markers of bone formation and resorption. Enzyme activities and numbers of active canals were also not increased with the concurrent treatment, but there was still an increase in the osteon diameter. As previously shown for cancellous bone, estrogen withdrawal increased cortical bone turnover. We have now shown that resorption depth within Haversian systems was also increased with treatment. The enhanced TRAP activity in individual osteoclasts supports the concept that osteoclasts are more active following estrogen withdrawal in agreement with theoretical arguments advanced previously. Understanding the cellular and biochemical mechanisms responsible for increased depth of osteoclast resorption when estrogen is withdrawn may allow the development of new strategies for preventing postmenopausal bone loss.